IDENTIFIKASI BAURAN PROMOSI DAN MINAT WISATAWAN BERKUNJUNG KE WISATA KULINER (Studi Kasus Kunjungan Aktor Ternama Gavin Casalegno di Kafe Gigi Susu, Canggu, Bali) (Jurnal Destinasi Pariwisata, 2026)
This study aims to identify the promotional mix and visitor interest in the Milk Tooth Cafe culinary destination located in Canggu, Bali. The focus of the study was directed at the viral phenomenon of the visit by the famous American actor, Gavin Casalegno, which had a significant impact on the cafe's image and popularity. This study used qualitative research methods with data collection techniques through observation, semi-structured interviews, documentation, and literature review.The results indicate that Milk Tooth Cafe implemented a promotional mix consisting of five main components: advertising, sales promotion, public relations, personal selling, and direct marketing. Digital advertising through collaboration with influencers proved to be the most effective strategy in attracting tourists, especially in the era of social media use to enhance the brand image and popularity of culinary tourism businesses. Furthermore, based on Ferdinand's (2002) theory of visitor interest, it was found that preferential interest had the strongest influence, with many visitors coming due to emotional connections with Gavin Casalegno and growing viral trends on TikTok and Instagram. These findings suggest that celebrity-based promotions and digital media can significantly increase the appeal of culinary tourism destinations. This research is expected to be a reference for culinary business actors in implementing effective promotional strategies to increase competitiveness in the tourism industry.This study is expected to serve as a reference for culinary business actors in implementing effective promotional strategies to enhance competitiveness in the tourism industry, especially in the rapidly developing digital era. By optimizing the right promotion mix, business actors can create synergy between marketing factors and consumer preferences to achieve maximum business objectives.
Keywords: Promotional Mix; Visiting Interest; Culinary Tourism; Influencer